Multilingual Education and Language Policy in a Globalized World: Toward Inclusive and Equitable Learning Systems - Joshi Rajkumar Harkishan (International Journal of Education Sciences, 2026)
Multilingual education involves teaching and learning in two or more languages, promoting linguistic diversity and enhancing educational outcomes. It acknowledges learners’ native languages and integrates them with dominant or global languages to foster inclusivity and cognitive development. Multilingual education (MLE) serves as a critical framework for promoting inclusivity and equity within increasingly globalized and culturally diverse classrooms. This paper explores the role of MLE and the influence of language policies on educational outcomes, social integration, and the preservation of linguistic diversity. Its significance lies in identifying strategies and frameworks to establish inclusive and equitable learning systems. Using a qualitative methodological framework that includes a comprehensive literature review and policy analysis across diverse global contexts, the research examines how educational systems can recognize linguistic diversity as an asset rather than a barrier. The study is grounded in sociolinguistic theories, such as language rights and the language ecology framework, highlighting that proficiency in multiple languages enhances cognitive flexibility and academic performance. Comparative case studies from Canada, India, South Africa, and Switzerland reveal varying degrees of success in policy implementation. While models like Switzerland’s demonstrate successful integration through strong governmental commitment, other nations face significant implementation gaps. Primary challenges identified include political resistance, resource constraints, inadequate teacher training, and entrenched ideological biases that favor dominant global languages over mother tongues. To foster more equitable learning systems, the paper recommends the adoption of additive multilingualism models that validate learners’ native languages while facilitating the acquisition of additional languages. Key strategies for policymakers include sustained financial investment, culturally responsive teacher preparation, and the development of flexible, contextually relevant curricula. Ultimately, the research concludes that embracing multilingual education is essential for fostering social cohesion and preparing students to navigate an interconnected world.
Keywords: Educational policies; educational strategies and frameworks; inclusive and equitable learning; linguistic diversity; multilingual education